Estimating the effect of democracy, governance and militarisation on peace in Africa - Chimere Okechukwu Iheonu; Kingsley O. Odo; Davidmac O. Ekeocha (African Governance and Development Institute (AGDI), 2020)
Peace has been deemed paramount to socioeconomic progress and economic development across nations. It is for this reason nations strive to improve the peaceful coexistence of citizens. This study investigates the effect of democracy, governance and militarisation on peace in 43 African countries for the year 2018 in a cross sectional framework. The Ordinary Least Square (OLS), the Tobit regression and the Quantile Regression (QR) were employed as estimation strategies. The empirical results firstly reveal that democracy increases peace in Africa, particularly in countries where the initial level of peace is at its highest level. Secondly, militarisation of Africa reduces peace in the region only in countries where the initial level of peace is at its highest level. Thirdly, the influence of governance on peace in Africa depends majorly on the measure of governance utilised. The control of corruption, government effectiveness and regulatory quality increase peace where the initial level of peace is at its lowest level. Political stability increases peace across the entire quantiles utilised while rule of law increases peace in countries where the initial level of peace is low. In conclusion, governance in general increases peace in the countries where initial level of peace is very low. Policy recommendations based on these findings are discussed.
Keywords: 330; Democracy; Governance; Militarisation; Peace; Africa